Driving Social Sustainability and Resilience of SMEs Amidst Turbulence: The Role of Information Technology and Dynamic Capabilities - Le,Bao Toan; Liu,Xinying (2024)
Research background and purpose: Amidst turbulences, there is an increasing recognition of capabilities factors in driving SMEs’ resilience. Besides, turbulences have casued difficulties for SMEs in sustaining their social sustainable practices, resulting in adverse effects on employees and society at large. Thus, SMEs need to leverage their capabilities to enhance their resilience and contribute to fair labor practices and local communities. This research aim to investigate the relationships between capabilities, resilience, and social sustainability in SMEs amidst turbulence. Theoretical framework: Based on the resource-based view (RBV) theory and dynamic capabilities view (DCV), three hypotheses were proposed to examine the relationships between the four factors: IT capabilities, dynamic capabilities, resilience, and social sustainability. In addition, two hypotheses were formed to evaluate the mediating role of organizational resilience. Methodology: This study applied the explanatory sequential mixed methods, with a focus on the quantitative approach. The PLS-SEM technique was implemented to analyze data collected from 81 managers working at SMEs in Vietnam to test the five proposed hypotheses. The qualitative method, with multiple-case approach, was implemented to interview seven companies’ representatives to seek explanations for the deviating result from the quantitative phase. Findings: There was a positive relationship between resilience and social sustainability. Besides, while the positive connection between dynamic capabilities and resilience was formed, IT capabilities did not link with organizational resilience. In addition, this study indicated four elements hindering the role of IT capabilities in enhancing SMEs’ resilience, which were industry and size, internal factors, alternative resources and capabilities, and time lags. Implications: This study contributes to the scarce litarature connecting social sustainability with other organizational factors. This study also enriches understandings of DCV as a theory complementing the RBV. Furthermore, empirical results diversify the current literature on IT capabilities, highlighting the variability in the role of this capability among firms. This study provides practical recommendations for SMEs’ managers to bolster resilience and promote social sustainability amidst turbulence.
Keywords: social sustainability; organizational resilience; information technology; dynamic capabilities; turbulence